Semiactive Vibration Control Using a Magnetorheological Damper and a Magnetorheological Elastomer Based on the Bouc-Wen Model - Wei Zhu; Xiao-ting Rui (Shock and Vibration)
A vibration control system is put forward using a magnetorheological damper (MRD) and a magnetorheological elastomer (MRE) connected in series. In order to model the hysteresis of the MRD, a Bouc-Wen model and a corresponding parameter identification method are developed for the MRD. The experimental results validate the proposed Bouc-Wen model that can predict the hysteretic behavior of the MRD accurately. The role of the MRE is illustrated by an example of a single degree-of-freedom system. A semiactive vibration control strategy of the proposed vibration control system is proposed. To validate this new approach, experiments are conducted and the results highlight significantly improved vibration reduction effect of the proposed vibration control system than the vibration control system only using the MRD.